Fixed Dose Combination for TB treatment (Faculty of Medicine Universitas Indonesia, 2003)
According to the World Health Organization, a third of the worldâs population is infected with tuberculosis. The disease is responsible for nearly 2 million deaths each year and over 8 million were developing active diseases. Moreover, according to WHO (2000), tuberculosis deaths are estimated to increase to 35 million between 2000-2020. The majority of tuberculosis patients worldwide are still treated with single drugs, or with 2-drug fixed-dose combinations (FDCs). To improve tuberculosis treatment, 2- and 3-drug FDCs were recommended by the World Health Organization (WHO) as part of the DOTS strategy. Since 1999 a 4-drug FDC was included on the WHO Model List of Essential Drugs. Today, FDCs are important tools to further improve the quality of care for people with TB, and accelerate DOTS expansion to reach the global TB control targets. Fixed dose combination TB drugs could simplifies both treatment and management of drug supply, and may prevent the emergence of drug resistance .Prevention of drug resistance is just one of the potential benefits of the use of FDCs. FDCs simplify administration of drugs by reducing the number of pills a patient takes each day and decreasing the risk of incorrect prescriptions. Most tuberculosis patients need only take 3â4 FDCs tablets per day during the intensive phase of treatment, instead of the 15â16 tablets per day that is common with single-drug formulations It is much simpler to explain to patients that they need to take four tablets of the same type and colour, rather than a mixture of tablets of different shapes, colours and sizes. Also, the chance of taking an incomplete combination of drugs is eliminated, since the four essential drugs are combined into one tablet. FDCs are also simpler for care-givers as they minimize the risk of confusion. Finally, drug procurement, in all its components (stock management, shipping, distribution), is simplified by FDCs. Adverse reactions to drugs are not more common if FDCs are used. Nevertheless, whenever side-effects to one or more components in a FDC are suspected, there will be a need to switch to single-drug formulations. Quality, safety and efficacy of FDC drugs are determined by the manufacturing process i.e. by compliance of the manufacturer with the requirements of good manufacturing practices (GMP) and pharmacopoeial specifications. National TB programmes must establish a QA system WHO established a laboratory network that tests the quality of FDCs in the marketplace and registers products upon request from the pharmaceutical industry. (Med J Indones 2003; 12: 114-9) Keywords: fixed dose combination, tuberculosis, treatment